Gypscie-KG: Building a Logic-Based Approach for Knowledge Graph Data Integration View in ML Systems - Moraes, Gabriela; Porto, Fabio; Ulliana, Federico; Baget, Jean-François; Leclère, Michel; Bisquert, Pierre; Gonçalves, Bernardo; Valduriez, Patrick (Anais Estendidos do Simpósio Brasileiro de Banco de Dados (SBBD), 2025)
This paper presents Gypscie-KG, a system that integrates heterogeneous machine learning (ML) data into a knowledge graph (KG) using logicbased rules to enable semantic queries and reasoning. It also explores the use of ChatGPT to support relational-to-graph schema mapping, demonstrating AI’s potential in declarative data integration for complex ML systems.